Web portal for scientific computing library - Abdul Basitt, Umi Nadia (2009)
Scientific computing or computational science is a collection of tools, techniques and theories required to develop and solve mathematical models in science and engineering on a computer. There are many systems of scientific computing libraries developed nowadays, regardless of whether they are web-based or web application. However, the libraries are complex and not complete. In addition, most science teams collaborate across multiple geographically distributed institutions, therefore, it becomes more difficult to store, share and analyze the scientific data among the team members. By developing this Web Portal for Scientific Computing Library, good criteria of scientific computing library are identified. This project aims to provide sophisticated web portal to store codes, share results, and share knowledge on scientific computing. Furthermore, the scientific computing library focuses on multi-domain applications. The technologies used for this web portal development are ASP.Net as the scripting language with use of Microsoft Visual Studio 2008 and Microsoft SQL Server 2005 as the database application development software. The data set used is sequential algorithm in C and C++ programming language based on numerical simulation of partial differential equation. It is hoped that this project will give benefits to the scientists who utilize the scientific computing for their researches.